Association of nonfasting vs fasting lipid levels with risk of major coronary events in the Anglo-Scandinavian cardiac outcomes trial-lipid lowering arm - Mora,S; Chang,CL; Moorthy,MV; Sever,PS (JAMA Internal Medicine, 2019)
Importance: Recent guidelines have recommended nonfasting for routine testing of lipid levels based on comparisons of nonfasting and fasting populations. However, no previous study has examined the association of cardiovascular outcomes with fasting vs nonfasting lipid levels measured in the same individuals. Objective: To compare the association of nonfasting and fasting lipid levels with prospectively ascertained coronary and vascular outcomes and to evaluate whether a strategy of using nonfasting instead of fasting lipid level measurement would result in misclassification of risk for individuals undergoing evaluation for initiation of statin therapy. Design, Setting, and Participants: This post hoc prospective follow-up of a randomized clinical trial included 8270 of 10305 participants from the Anglo-Scandinavian Cardiac Outcomes Trial-Lipid Lowering Arm (ASCOT-LLA) with nonfasting and fasting lipid levels measured 4 weeks apart (including 6855 participants with no prior vascular disease) (median follow-up, 3.3 years; interquartile range, 2.8-3.6 years). Data were collected from February 1, 1998, to December 31, 2002, and analyzed from February 1, 2016, to November 30, 2018. Multivariable Cox models, adjusted for cardiovascular risk factors, were calculated for 40-mg/dL (1-mmol/L) higher values of nonfasting and fasting lipids. Main Outcomes and Measures: The trial's primary end point consisted of major coronary events (nonfatal myocardial infarction [MI] and fatal coronary heart disease [212 events]). Secondary analyses examined atherosclerotic cardiovascular disease (ASCVD) events (including MI, stroke, and ASCVD death [351 events]). Results: Among the 8270 participants (82.1% male; mean [SD] age, 63.4 [8.5] years), nonfasting samples had modestly higher triglyceride levels and similar cholesterol levels compared to fasting samples. Associations of nonfasting lipid levels with coronary events were similar to those for fasting lipid levels. For example, adjuste